Dust Exposure and Lung Function Disorders - Mona Lestari; Poppy Fujianti; Novrikasari Novrikasari; Rizka Faliria Nandini (Respiratory Science, 2023)
Dust is a particle floating in the air produced due to mechanical processes such as splitting, grinding, grinding, punching or blasting, cutting and destroying material. Dust particles in the air for a relatively long time can enter the human body through breathing. Dust less than 5 µm entering the human respiratory system can reach the inside of the lungs or alveoli can cause lung function disorders. Impaired pulmonary function is the inability to develop (elasticity) of the lungs as well as disorders of the respiratory tract both structural (anatomical) and functional which causes slowing of respiratory airflow. The International Labor Organization (ILO) defines pulmonary dysfunction as the accumulation of dust in the lung tissue and lung tissue reaction to the dust accumulation. Dust entering the alveoli can cause hardening of the tissue (fibrosis) and if 10% of the alveoli is hardening, it will reduce its elasticity in accommodating the volume of air so that the ability to bind oxygen is decreased. This condition causes a reduction in the supply of oxygen absorbed by blood capillaries to the brain tissue, heart, and other body parts.